Revision of Neotropical wolf spider genus Arctosa C.L. Koch, 1847 (Araneae: Lycosidae), with description of seven new species - Paredes-Munguía, Williams; Brescovit, Antonio D.; Teixeira, Renato A. (Zootaxa, 2024)
The genus Arctosa C.L. Koch is redescribed and diagnosed. Seven new species are described, four of them based on both sexes (A. conflicta sp. nov., A. costenola sp. nov., A. jibarosa sp. nov. and A. villa sp. nov.), two only on females (A. ayaymama sp. nov. and A. mineira sp. nov.), and one only on the male (A. pacaya sp. nov.). We also propose the transference of Arctosa humicola (Bertkau, 1880) and Arctosa fusca (Keyserling, 1877) to Trochosa C.L. Koch, 1847, and the new synonymy of Arctosa inconspicua (Bryant, 1948) with Trochosa humicola (Bertkau, 1880) comb. nov. Besides, Arctosa andina (Chamberlin, 1916) and Arctosa pugil (Bertkau, 1880) are transferred to Hogna Simon, 1885, and Arctosa aussereri (Keyserling, 1877) to Prolycosides Mello-Leitão, 1942. Additionally, eight lycosid species are synonymized with Prolycosides aussereri: Schizocosa proletaria (Tullgren, 1905); Arctosa workmani (Strand, 1909); Hogna planithoracis (Mello-Leitão, 1938); Hogna variolosa (Mello-Leitão, 1941); Megarctosa melanostoma (Mello-Leitão, 1941); Hippasosa huachoi (Mello-Leitão, 1942); Pirata abalosi (Mello-Leitão, 1942); and Pirata soukupi (Mello-Leitão, 1942). We also transfer Trochosa tenebrosa Keyserling, 1877 to Arctosa. The males of Arctosa tenebrosa (Keyserling, 1877) comb. nov. and Trochosa humicola (Bertkau, 1880) comb. nov. are described for the first time.